Implications of the Western Diet for Agricultural Production, Health and Climate Change - Vega Mejía, Natalia; Ponce Reyes, Rocio; Martinez, Yuriana; Carrasco, Omar; Cerritos, René (Frontiers in Sustainable Food Systems, 2018)
Our current eating habits affect not only our health but also the environment and agricultural production. Previous studies have shown the relationship between our eating habits and each of these three topics independently. Here we analyzed the links between health, agricultural production and environmental data together, using global databases. We found the Western diet – dominated by processed foods, refined sugar, fats and flours – has negative implications for all three. Increased production and consumption of sugar and refined grains over the last 40 years correlates with negative human health outcomes globally: an alarming increase in diseases such as diabetes, overweight and obesity. In addition to these health effects, the Western diet relies on methods of agricultural production that negatively impact ecosystems, increase the use of fossil fuels and boost greenhouse gas emissions (GHGe). Ancestral communities around the world consume a greater variety of plant and animal species (including insects) than Western urban populations, with positive health and environmental outcomes. Processed food, on the other hand, comes at a high environmental cost: it generates high GHGe, accelerates land-use change to support agriculture and intensive livestock activities, and requires huge amounts of water and agrochemicals. Changing the Western diet could substantially reduce diabetes, obesity, and GHGe. Consuming insects and a wider variety of plant species could improve health outcomes and reduce some of the environmental impacts of agricultural production.